Beliefs and attitudes towards mental illness: an examination of the sex differences in mental health literacy in a community sample - Gibbons, Raymond J. (PeerJ, 2015)
Objectives. The current study investigated mental health literacy in an Australian sample to examine sex differences in the identification of and attitudes towards various aspects of mental illness. Method. An online questionnaire was completed by 373 participants (M = 34.87 years). Participants were randomly assigned either a male or female version of a vignette depicting an individual exhibiting the symptoms of one of three types of mental illness (depression, anxiety, or psychosis) and asked to answer questions relating to aspects of mental health literacy. Results. Males exhibited poorer mental health literacy skills compared to females. Males were less likely to correctly identify the type of mental illness, more likely to rate symptoms as less serious, to perceive the individual as having greater personal control over such symptoms, and less likely to endorse the need for treatment for anxiety or psychosis. Conclusion. Generally, the sample was relatively proficient at correctly identifying mental illness but overall males displayed poorer mental health literacy skills than females.